Isolation and Identification of Hydrocarbon-Degrading Bacteria from Polychaete Marphysa moribidii - Fazilah Ariffin; Rozilawati Mohamed Razali; Vigneswari Sevakumaran (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2021)
Marine contamination caused by anthropogenic activities has side effects and causes severe contamination to the environment. Polychaetes are benthic organisms that live in the sediment and can be a good indicator of sediment contamination by organic compounds. In this study, bacterial strains were isolated and identified from the gut of polychaete worm Marphysa moribidii and the potential of the bacteria was evaluated to degrade hydrocarbon compounds. The isolated bacteria were primary and secondary screened on Minimal Salt Media (MSM) agar supplemented with 1% v/v of diesel oil. Diesel degradation analysis was performed by inoculating potential bacterium into MSM broth with 1% v/v diesel oil and incubated at 37 oC for 20 days. Diesel degradation percentage was analyzed using the gravimetric method, while the bacteria cell densities were measured using the standard plate count method. Then, the selected isolates were identified based on their morphological characteristics and 16S rDNA sequences. As a result, two bacteria isolates coded as Isolate 6 and Isolate 8 were able to degrade diesel oil up to 52.29% and 39.24% after 20 days of incubation. The 16S rDNA sequence analysis revealed that it was identified as Bacillus sp. strain UMTFA1 (RB) and Staphylococcus kloosii strain UMTFA2 (RS). Our result showed that these strains have the potential in oil-degrading processes, which will provide new insight into bioremediation process and decrease environmental pollution in soil and water contaminated with hydrocarbons.